Review of Effectivity Graphite Anode for Impressed Current Cathodic Protection (ICCP) on Reinforced Concrete - Nurcholis , Herlan; Laksita , Amanta Ptri; Astuti, Pinta (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2025)
Reinforced concrete is one of the essential elements in the construction field, especially in infrastructure buildings. The metal reinforcement in concrete, one of which is iron, has the weakness of being prone to corrosion. Corroded reinforcement cannot withstand the planned load and cannot meet the service life of the building. Thus, the process of corrosion must be slowed down or controlled. Currently, many studies are being conducted to find new methods for preventing corrosion, one of which is the Impressed Current Cathodic Protection (ICCP) method. Graphite is a material that can be used as an anode for cathodic protection using the ICCP method. Graphite is a form of carbon that has high porosity and thermal conductivity, allowing it to function as a current conductor. Graphite is immune to chloride, making it suitable for use as an anode.